Comment on "Graphene oxide regulates the bacterial community and exhibits property changes in soil" by J. Du, X. Hu and Q. Zhou, RSC Advances, 2015, 5, 27009. Issue 56 (26th May 2016) - Forstner, Christian; Wang, Peng; Kopittke, Peter M.; Dennis, Paul G.
Abstract : Here we question the validity of a recent claim that addition of graphene oxide to soil promotes bacterial diversity. Abstract : Human society is dependent on the provision of ecosystem goods and services mediated by soil organisms. It is important, therefore, to determine whether new and emerging materials influence the structure and function of soil biological communities. A recent study concerning the fate of the emerging nanomaterial, graphene oxide, in soil concluded that it promotes bacterial diversity. Here we demonstrate that due to issues with their experimental design and data analysis, their claim is unjustified.